2014
DOI: 10.3892/ijmm.2014.1711
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α promotes gallbladder cancer cell growth and invasion through autocrine mechanisms

Abstract: Tumor necrosis factor-α (TNF-α) has been suggested to be a putative tumor promoter gene, and autocrine of TNF-α expression has been found in colon cancer and ovarian cancer. As the role of autocrine TNF-α in human gallbladder cancer has not yet been elucidated, the present study examined the expression of TNF-α in gallbladder cancer-derived cell lines. Based on the data, TNF-α mRNA and TNF-α protein expression differed significantly different between the cell lines. In addition, using siRNA targeting TNF-α, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 29 publications
4
44
0
3
Order By: Relevance
“…NF-κB activation is involved in cancer crosstalk inflammation, and the inflammation in turn promotes tumor progress, as evidenced by results in an animal model and cell experiments [21,22]. In our previous study [23], we demonstrated that activation of NF-κB plays an important role in gallbladder cancer progression.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…NF-κB activation is involved in cancer crosstalk inflammation, and the inflammation in turn promotes tumor progress, as evidenced by results in an animal model and cell experiments [21,22]. In our previous study [23], we demonstrated that activation of NF-κB plays an important role in gallbladder cancer progression.…”
Section: Introductionmentioning
confidence: 76%
“…Western blot analysis was performed as described before [23]. The following primary antibodies were used from the different companies under listing respectively: mouse monoclonal anti-human RIP-1 antibody(1:1000), rabbit polyclonal anti-human VEGF-C antibody(1:1000), monoclonal rabbit anti-human c-Jun(AP-1)(1:1000), and monoclonal rabbit anti-human p-c-Jun(p-AP-1)(1:1000) (all from Abcam biotechnolgoy), monoclonal mouse anti-human AKT (1:500), monoclonal mouse anti-human p-AKT (1:500), mono-clonal mouse anti-human nuclear factor-κB (NF-κB) (p65)(1:500), monoclonal mouse anti-human p-NF-κB (p-p65) (1:500) (all from Cell Signaling Technology, Danvers, MA, USA), monoclonal mouse anti-human β-actin(1:1500) ( from Santa Cruz Biotechnology, Inc. Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA reactions were performed for 10 minutes at 25°C, followed by 1 hour at 42°C and 10 minutes at 72°C. As a template, 2.5 µl of cDNA were used for standard polymerase chain reaction (PCR) with following specific primers (all primers were customized by Eurofins MWG GmbH, Ebersberg, Germany): eGFP (sense: 5′‐CTA TAT CAT GGC CGA CAA GCA GA‐3′; antisense: 5′‐GGA CTG GGT GCT CAG GTA GTG G‐3′; amplification product 165 bp) mcherry (sense: 5′‐TTC ATG TAC GGC TCC AAG GC‐3′; antisense: 5′‐CTG CTT GAT CTC GCC CTT CA‐3′; amplification product 297 bp) syncytin‐1 (sense: 5′‐AGG AGC TTC GAA ACA CTG GA‐3′; antisense: 5′‐GTG AGC TAA GTT GCA AGC CC‐3′; amplification product 494 bp ) ASCT2 (sense: 5′‐GAC CGT ACG GAG TCG AGA AG‐3′; antisense: 5′‐GGG ACG CAG CAG AAC ATT AT‐3′; amplification product 445 bp ) syncytin‐2 (sense: 5′‐AGC AGC CGT AGT CCT TCA AA‐3′; antisense: 5′‐AGG GGA AGA ACC CAA GAG AA‐3′; amplification product 231 bp ) MFSD2A (sense: 5′‐CTC CTG GCC ATC ATG CTC TC‐3′; antisense: 5′‐GGC CAC CAA GAT GAG AAA‐3′; amplification product 129 bp) TNF‐α (sense: 5′‐AGT GAC AAG CCT GTA GCC C‐3′; antisense: 5′‐GCA ATG ATC CCA AAG TAG ACC‐3′; amplification product 443 bp ) TNFR1 (sense: 5′‐TGC CAG GAG AAA CAG AAC A‐3′; antisense: 5′‐AAC CAA TGA AGA GGA GGG AT‐3′; amplification product 223 bp ) TNFR2 (sense: 5′‐TCC CAA GCC AGC TCC ACA ATG‐3′; antisense: 5′‐AGG GGC AGG GGC TTC TCT TC‐3′; amplification product 158 bp ) GAPDH as a control (sense: 5′‐ACC ACA GTC CAT GCC ATC AC‐3′; antisense: 5′‐TCC ACC ACC CTG TTG CTG TA‐3′; amplification product 452 bp ). …”
Section: Methodsmentioning
confidence: 99%
“…Treatment of low‐dose deguelin completely blocked TNF‐α‐induced invasion of SAS cells (Figure A). It has been shown that TNF‐α triggers invasion of cancer cells by activation of NF‐κB and its downstream target genes that are involved in cell mobility . As shown in Figure B, the ectopic expression of IKKβ alone (without deguelin treatment) did not affect the invasion ability of SAS cells compared to the vector‐only group.…”
Section: Resultsmentioning
confidence: 84%